Electrochemical properties of corrosion products formed on Zn‐Mg, Zn‐Al and Zn‐Al‐Mg coatings in model atmospheric conditions. Issue 8 (16th February 2015) - Stoulil, J.; Prosek, T.; Nazarov, A.; Oswald, J.; Kriz, P.; Thierry, D.
<x xml:space="preserve">Abstract</x> The electrochemical properties of corrosion products formed under sodium chloride deposits on zinc coatings alloyed with aluminium and magnesium have been studied using impedance spectroscopy (EIS), scanning Kelvin probe (SKP) and photoluminescence (PL) techniques. The low‐energy band gap identified in corrosion products on hot‐dip galvanized steel was associated with their higher electric conductivity and efficiency of the rate‐controlling oxygen reduction reaction. It was attributed to the presence of ZnO, zincite. The formation of ZnO was hindered by the alloying. The alloyed coatings were covered by more compact layers of corrosion products with lower electric conductivity and better barrier properties.